Video Support in Problem-Based Learning to Facilitate of Elementary Students' Numeracy Abilities Improvement - Qadri, Mila; Krismanto, Wawan; Zainal, Zaid (Universitas Pendidikan Ganesha, 2023)
The problem of this research is the low numeracy skills of the fifth grade students of elementary school. Because of that, this study aims to examine the implementation of Problem-Based Learning (PBL) with video media to improve the numeracy skills of elementary school students. The approach is qualitative with the type of classroom action research (CAR). The research subjects were 18 students and one teacher of the fifth grade of elementary school. This research was conducted in two cycles on the material for solving math word problems. Each cycle is completed in two learning meetings. Research data was obtained through observation techniques, tests, and documentation. The data analysis procedures used are condensation, data presentation, and conclusion. The results showed that the learning process using video-assisted PBL showed changes in learning focus, learning activities, engagement, interaction, and collaboration in solving problems. The students' numerical abilities category has increased from 61% of students in the high and medium categories in Cycle I to 89%.Thus, implementing the PBL learning model assisted by video media can improve the learning process and students' numeracy abilities in solving math word problems in the fifth grade of elementary school. The implication is that relevant learning media should support the PBL learning model. Implementing PBL assisted by video media needs to be used as an alternative to overcoming the problem of low students' numeracy skills in elementary schools.